Jurnalis Dan Terorisme (Studi Pustaka Etika Jurnalis Dalam Meliput Dan Memberitakan Kasus Terorisme Di Media Siber) - Nadhiroh Nadhiroh (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
The media plays an important role in reporting terrorism events. Journalists in print, electronic and online have ethics which are ideally carried out when covering and reporting terrorism cases. However, as the development of the digital era requires some media to quickly convey information, it makes some journalists lack the discipline to obey applicable ethics. This article examines the literature study of journalist ethics in covering and reporting on terrorism cases in the digital age. The method used in this research is a literature study on the regulations related to journalist code of ethics in reporting and reporting on terrorism cases in the cyber media.